PERAN CUSTOMER EXPERIENCE TERHADAP LOYALTY, WORD OF MOUTH DAN RETENTION MELALUI RELATIONSHIP QUALITY - Dian Anggraini Puspitasari; Unggul Kustiawan (MANAJEMEN DEWANTARA, 2023)
Customer experience with a positive value will increase loyalty to bank service providers if it leads to relationship quality so that it will avoid churnout from potential customers and provide sustainable growth for the company. The purpose of this study was to determine the role of the bank's customer experience in influencing loyalty, word of mouth and retention supported by the intervening relationship quality variable. This research is a quantitative research using the Structural Equation Model (SEM) method which was processed using PLS 3. Respondents in this study were customers of Bank BUMN and had filled out questionnaires online. The results of this study are that customer experience has a positive and significant effect on loyalty, word of mouth and retention through relationship quality as a mediating variable. This research has important managerial implications for companies, especially marketing management in making developing business strategies by considering aspects of Customer Experience and Relationship Quality so that the company's goals are to increase transactions, build long-term relationships with consumers and have a competitive advantage in market can be reached.